ANALYSIS BEHIND THE SLOPE STABILITY IN THE LIMESTONE QUARRY BLOK MLIWANG TIMUR PT. SEMEN INDONESIA (PERSERO) TBK. TUBAN, JAWA TIMUR - Agus Salim (NAROTAMA UNIVERSITY, Indonesia)
Clay mining activities at PT. Semen Indonesia (Persero) Tbk uses a Surface Mining system with tiered or layered mining methods. The clay mining activity in east kuari mliwang has produced 4-6 layers from the lowest elevation which is +0 meters above sea level (masl), with the opening of an area of ??27 hectares, from the results of mining that has been done. Each slope made must have safety factors that meet the standards set by the Ministry of Energy and Mineral Resources and the Indonesian National Standard (SNI) taking into account the efficiency of reserves that will be in the mine. The return analysis of slope stability was obtained based on the value of the safety factor of a slope using the Bishop Simplified method with the help of Rocscience Slide v6.0 software. Input data in the form of physical and mechanical properties obtained from laboratory testing. Determination of minimum safety factors using SNI 8460: 2017, ICS 91.010.01 for soil material, namely FK ? 1.5. The factors that affect slope stability at the study site are the physical and mechanical properties of the soil, the slope geometry, and the condition of the ground water table. The results of the calculation of slope stability safety factors at the study site have different results, for Block T-03, slopes with an overall height of 21 m, the overall slope angle of 27 ° has a FK value = 1.502. Block W-06, Slope with an overall height of 25 m, the overall slope angle of 27 ° has a FK value = 1.504. And Block Z-04, Slope with an overall height of 26 m, the overall slope angle of 30 ° has a FK value = 1.508. From the calculation results the average location of the study has a value of FK ? 1.5 which indicates the slope is in a stable condition.